Analisis Desain Pondasi Rakit untuk Bangunan Bertingkat dengan Metode Konvensional - Bahagianda, Dhyna Annisa Maghfira; Setyanto, Setyanto; Adha, Idharmahadi (Universitas Lampung, 2017)
The foundation of the building is usually divided into two parts: shallow foundation and deep foundation, depending on the location of hard soil and the depth ratio with the width of the foundation (D ≤ B). The foundation of this raft serves to mediate the surface of one or more columns within several lines or paths with the ground. The use of the raft foundation is used when the decline is a problem eg in soft soil. The foundation of raft becomes alternative choice seen from external factor that is implementation process which do not give impact to surrounding environment or building around it. In this study conducted data collection obtained from the results of laboratory tests in the form of data sondir results, SPT results and data in the form of load structures and field load tests and building analysis load. From the laboratory results and the subsequent building load, the calculation of the force field with the SAP 2000 program, calculate the maximum carrying capacity of the raft foundation under review, calculate the decline of the raft foundation and obtain the result of the structural requirements of the raft foundation. Based on the results of the analysis in this study found the carrying capacity of soil for raft foundation of 907.643 kN/m2. While the maximum voltage distribution at the base of the raft foundation due to the load and moment is 38.0696 kN/m2. Keywords: Raft Foundation, Bearing Capacity, Reinforcement